POLA ASUH ORANG TUA TERHADAP ANAK DISABILITAS: Perspektif Nilai-Nilai Keagamaan - M. Yusuf M.Yusuf (Al-Thifl: Jurnal Pendidikan Anak Usia Dini, 2024)
Parenting of children with disabilities is very necessary, especially children with disabilities who really expect special attention, sometimes some parents do not accept children with disabilities well because children with disabilities are considered a disgrace and so on, even though children are purely God's gift to parents who are able to care for them. However, parents are reluctant to even care for children with disabilities properly. Therefore, it is necessary to understand and care for children with disabilities with more attention. This study aims to find out the parenting patterns of parents of children with disabilities from a religious perspective and to find out the challenges in caring for people with disabilities. In this study, the method used is a qualitative approach while the data collection technique is carried out by observation, interview and documentation. The results found are parenting patterns and the level of understanding of parents of children with disabilities argue that children with disabilities are children entrusted by God who need to be grateful and not a disgrace that must be covered, in their coaching or parenting, indeed to foster children with disabilities need more attention and affection for them, need patience and perseverance, because the characters of children with disabilities are different, of course their behaviour is also different, as for the challenges, children with disabilities are more difficult to manage, let alone difficult to understand the sign language they convey.